2010
DOI: 10.1002/chem.201001335
|View full text |Cite
|
Sign up to set email alerts
|

New Tris(hydroxypyridinones) as Iron and Aluminium Sequestering Agents: Synthesis, Complexation and In Vivo Studies

Abstract: Two new tripodal tris(3-hydroxy-4-pyridinone) hexadentate chelators-NTA(BuHP)(3) and NTP(PrHP)(3) (NTA=nitrilotriacetic acid, NTP=nitrilotripropionic acid, HP=hydroxypyridone)-have been developed and studied in solution for their iron and aluminium binding affinity, and also assayed in vivo for their capacity to remove metal from an animal model that is overloaded. These chelators are positional isomers, possessing identical general structures based on aminotricarboxylic acid skeletons attached to three bident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 46 publications
2
46
0
1
Order By: Relevance
“…Furthermore, a higher thermodynamic stability can be also expected for the NTP-than for the KEMPgallium complexes based on comparison with the corresponding iron complexes. In fact the corresponding pFe values differed on ca 1-order of magnitude [18], and identical behaviour can be expected for gallium systems due to the similarity of the ionic radius of these threecharged metal ions (Fe, 65 pm; Ga, 62 pm). It is also clearly shown that, for the micromolar conditions that prevail in biological systems, the tris-chelator NTP(PrHP) 3 presents a much higher metal chelating efficacy than the monohydroxypyridinone derivative, DFP, due to its higher denticity.…”
Section: Gallium Complexation Studiesmentioning
confidence: 73%
See 4 more Smart Citations
“…Furthermore, a higher thermodynamic stability can be also expected for the NTP-than for the KEMPgallium complexes based on comparison with the corresponding iron complexes. In fact the corresponding pFe values differed on ca 1-order of magnitude [18], and identical behaviour can be expected for gallium systems due to the similarity of the ionic radius of these threecharged metal ions (Fe, 65 pm; Ga, 62 pm). It is also clearly shown that, for the micromolar conditions that prevail in biological systems, the tris-chelator NTP(PrHP) 3 presents a much higher metal chelating efficacy than the monohydroxypyridinone derivative, DFP, due to its higher denticity.…”
Section: Gallium Complexation Studiesmentioning
confidence: 73%
“…The stepwise protonation constants are depicted in Table 1, which also includes the corresponding values for other tripodal compounds and deferiprone (DFP), aimed at comparative purposes. NTP(PrHP) 3 has seven dissociable protons (H 7 L 4+ ), and the protonation constants (log K i ) depicted in Table 1 are assigned as follows: the first three values correspond to the three hydroxyl groups of the HP moieties; the fourth value is due to the backbone apical ammonium group; the last three values are attributable to the pyridinium protons of HP moieties [18]. This Table also includes the octanol/water partition coefficients (log P) for this ligand and other HP compounds at the physiological pH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations